Going Concern Audit Opinion: The Mediating Role of Financial Distress on the Influence of Financial Ratios and Audit Report Lag - Aprillia, Fela; Suswati Risnaeni, Umi (Journal of Accounting and Finance Management, 2026)
This research is motivated by the increase in audit opinions going concern of companies which is reflected in the condition of financial difficulties to delisting. This study aims to analyze the role of financial distress on the influence of financial ratios and audit report lag on going concern audit opinions through a quantitative approach with secondary data from manufacturing companies listed in the Sharia Securities List for the 2022-2024 period. The research sample consisted of 32 companies selected using purposive sampling techniques. Data analysis was carried out through the evaluation of the measurement model using Partial Least Squares and testing the relationship between variables using logistic regression, considering that dependent variables are dichotomous. The results of the study show that financial ratios and audit report lag do not have a simultaneous or partial effect on the opinion of audit going concern. In addition, financial distress has not been able to mediate the relationship between independent variables and going concern audit opinions. These findings indicate that auditors consider other, more comprehensive factors in providing a going concern audit opinion.